Journalistic Ethics In Local News Coverage At Suarokito.Com - Jaya, Ade Agung Sutra; Narti, sri; Putra, Dilmai (Utami Publisher, 2025)
As journalism continues to evolve under the influence of digital technology, local media play an essential role in delivering relevant and credible information to their communities. One such media outlet in North Bengkulu is Suarokito.com, a digital platform dedicated to local reporting. This study analyzes the application of journalistic ethics in local news coverage on Suarokito.com, focusing on the principles outlined in the Indonesian Journalistic Code of Ethics: independence, professionalism, verification, balance, and protection of sources and privacy.This research adopts a qualitative normative approach, using in-depth interviews, participant observation, and content analysis of published news articles. The informants include reporters, editors, and the editor-in-chief of Suarokito.com. The findings show that Suarokito.com strives to uphold independence and professionalism, despite challenges such as pressure to publish news rapidly and limited resources. The principles of verification and balance are generally observed, with news articles undergoing fact-checking and using multiple sources. However, challenges persist, including the temptation to avoid unverified or sensational stories due to resource constraints. The study recommends regular ethical training for local journalists and the strengthening of internal mechanisms to maintain editorial integrity and news quality.